2017
DOI: 10.1186/s12929-017-0359-3
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin attenuates chronic hypoxia-induced pulmonary hypertension via adenosine A2A receptor-induced SDF-1/CXCR4/PI3K/AKT signaling

Abstract: BackgroundBaicalin, an important flavonoid in Scutellaria baicalensis Georgi extracts, exerts a variety of pharmacological effects. In this study, we explored the effects of baicalin on chronic hypoxia-induced pulmonary arterial hypertension (PAH) and investigated the mechanism underlying these effects. Moreover, we examined whether the inflammatory response was mediated by the A2A receptor (A2AR) and stromal cell-derived factor-1 (SDF-1)/C-X-C chemokine receptor type 4 (CXCR4)-induced phosphatidyl inositol-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Bleomycin has been reported to suppress pulmonary fibrosis through the A2A receptor and the SDF‐1/CXCR4 signaling pathway 32 . Besides, adenosine A2A receptor has been proved to mediate the SDF‐1/CXCR4/PI3K/AKT signaling pathways to regulate the progression of pulmonary hypertension 33 . However, the relationship among adenosine A2A receptor, SDF‐1 and CXCR4 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleomycin has been reported to suppress pulmonary fibrosis through the A2A receptor and the SDF‐1/CXCR4 signaling pathway 32 . Besides, adenosine A2A receptor has been proved to mediate the SDF‐1/CXCR4/PI3K/AKT signaling pathways to regulate the progression of pulmonary hypertension 33 . However, the relationship among adenosine A2A receptor, SDF‐1 and CXCR4 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…32 Besides, adenosine A2A receptor has been proved to mediate the SDF-1/ CXCR4/PI3K/AKT signaling pathways to regulate the progression of pulmonary hypertension. 33 However, the relationship among adenosine A2A receptor, SDF-1 and CXCR4 remains unclear. In our study, we firstly revealed the correlation among the adenosine A2A receptor, SDF-1 and CXCR4 in the lung-to-brain metastatic process.…”
Section: Parametersmentioning
confidence: 99%
“…The structures are shown in Figure 1. Some studies have shown that these ingredients influence the cardiovascular system (Cao et al, 2017;Gao, Chen, Liang, Xie, & Chen, 2015;Huang et al, 2017;Olaleye, Crown, Akinmoladun, & Akindahunsi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In other study [54], carried out in the same model of PH, showed that 2% baicalin solution downregulated the p38 mitogen-activated protein kinase MAPK/MMP-9 pathway and expression levels of MMP-9. Huang et al [51] observed additionally that baicalin (60 mg/kg i.p.) attenuated chronic hypoxia-induced PH via adenosine A2A receptor-induced SDF-1/CXCR4/PI3K/AKT signaling.…”
Section: In Vivo Studies Related To the Various Models Of Hypertensionmentioning
confidence: 96%
“…Baicalin has been widely studied in several in vitro and in vivo models and showed many activities such as: anti-viral [42], anti-oxidative via several pathways [43], neuroprotective and enhancin cognitive functions [44,45], anti-inflammatory [46], anti-cancer [47,48], and hepatoprotection [49]. In recent years, many studies showed anti-hypertensive properties of baicalin [46,[50][51][52][53][54][55][56][57][58][59][60], and also cardioprotective [50], antiplatelet, anticoagulant, and profibrinolytic activities [61].…”
Section: Influence In Pregnancymentioning
confidence: 99%